2012
DOI: 10.1108/00070701211202377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐harvest harpin and modified atmosphere packaging on quality of cherry tomato cultivars “Alona” and “Cluster”

Abstract: PurposeThe aim of this research is to determine the effects of pre‐harvest harpin (H) and modified atmosphere packaging (MAP) on the storage and fruit quality of cherry tomato (Lycopersicon esculentum Mill. cvs. “Alona” and “Cluster”).Design/methodology/approachH was used at 50 g 100 l‐1 concentration. First application was done on the seedlings in 3‐4 leaf stages and the other four applications were repeated at 20‐day intervals. Then, treated and untreated fruits were stored in plastic film materials with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
7
23
0
Order By: Relevance
“…The authors showed that the small grape tomatoes are very susceptible to water loss during handling and storage, which also contributes to a decrease in quality. Akbudak et al (2012) evaluated weight loss of cherry tomatoes in passive MAP using plastic film materials with various O 2 and CO 2 permeabilities and found that weight loss was significantly higher in tomatoes stored under normal atmosphere (NA) compared to MAP. In a similar study, Aguayo et al (2004) determined that the weight loss was lower in tomatoes wrapped with plastic film material -i.e., those whose atmospheric combinations were altered -compared with those stored unwrapped.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors showed that the small grape tomatoes are very susceptible to water loss during handling and storage, which also contributes to a decrease in quality. Akbudak et al (2012) evaluated weight loss of cherry tomatoes in passive MAP using plastic film materials with various O 2 and CO 2 permeabilities and found that weight loss was significantly higher in tomatoes stored under normal atmosphere (NA) compared to MAP. In a similar study, Aguayo et al (2004) determined that the weight loss was lower in tomatoes wrapped with plastic film material -i.e., those whose atmospheric combinations were altered -compared with those stored unwrapped.…”
Section: Resultsmentioning
confidence: 99%
“…Storage of pink 'Buffalo' tomatoes (Solanum lycopersicum) in 4% O 2 + 2% CO 2 at 12 C contributed to extending their shelf life (Nunes et al, 1996). In contrast, Ratanachinakorn et al (1997) found that pink 'Bermuda' tomatoes were not harmed by exposure to 0.5% O 2 for 1 day or 80% CO 2 for 2 days at 22 C. Akbudak et al (2012) studied the effect of a bioactivator derived from Erwinia amylovora, called harpin (H), and passive modified atmosphere packaging on cherry tomato quality. The authors found that these treatments were effective in retaining fruit quality.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Excessive field heat gives rise to an undesirable increase in metabolic activity and immediate cooling after harvest is therefore important [24]. Precooling minimises the effect of microbial activity, metabolic activity, respiration rate, and ethylene production [25], whilst reducing the ripening rate, water loss, and decay, thereby preserving quality and extending shelf life of harvested tomatoes [26].…”
Section: Precooling After Harvestmentioning
confidence: 99%
“…This increases the metabolic activity that should be reduced immediately after harvest. Pre-cooling minimizes the efect of microbial activity, metabolic activity, respiration rate, and ethylene production [8,9].…”
Section: Pre-cooling and Ield Heat Reduction After Harvestmentioning
confidence: 99%